Implementasi Prinsip Itikad Baik dalam Kontrak Bisnis: Perspektif Hukum Perdata - Citra Agung; Nena Anggraini; Brian Save Sitanggang; Fadila Ulfa; Sudawan Supriadi; Fachruddiansyah Muslim (Journal of Economics, Bussiness and Management Issues, 2026)
This study aims to analyze the implementation of the principle of good faith in business contracts from the perspective of civil law. The principle of good faith is one of the fundamental principles in contract law that ensures fairness, honesty, and balance between the parties involved in a contractual relationship. This research uses a normative juridical method with a statutory approach and a conceptual approach. The data used in this research are secondary data obtained from legislation, legal books, scientific journals, and other relevant legal documents related to civil law and contract law. The results of the study indicate that the principle of good faith plays a crucial role in every stage of a business contract, including the negotiation process, the formation of the contract, and the implementation of the agreement. In civil law, good faith is not only interpreted as honesty but also includes fairness, propriety, and responsibility in fulfilling contractual obligations. The proper implementation of the principle of good faith can prevent disputes and provide legal protection for the parties involved in business transactions. Therefore, the principle of good faith must be consistently applied in drafting and implementing business contracts to ensure justice, legal certainty, and balance for all parties.